Profile of patients with Down syndrome attended at UFRGS: an 18-year descriptive documentary evaluation - Cançado-Figueiredo, Márcia (2021)
Introduction: Evaluate the profile of patients with Down Syndrome (DS) assisted in the Discipline of Dental Care of Patients with Specials Needs in the School of Dentistry, at Federal University of Rio Grande do Sul (UFRGS). Method: Based on the dental records of patients treated at an outpatient level between 2001 and 2019, information was obtained regarding the patient's age in the first care, sex, form of access, systemic condition of DS, medication used, and treatment received on his last visit to the clinic. Result: DS represented 9% of patients, the prevalence of which was male (61%) and median age of 24 years. Regarding the conditions associated with DS, 2.8% presented autism and 15.9% had chronic diseases, with cardiopathy and hypothyroidism as the most prevalent. Related to the medicines of continuous use, 21.4% used medication, being the most frequent: antiepileptics, antipsychotics, anticonvulsants, antithyroid agents. Conclusion: The relevance of this article is made in view of the extreme importance of knowing, in depth, the condition of patients with Down Syndrome, because only in this way can be offered an adequate treatment, restoring and developing the health and life quality of themselves.